Cost per Quality Adjusted Life Years gained for Anterior Cervical Discectomy and Fusion for Degenerative Spine Disease in Elderly Population. Issue 1 (April 2016) - Chotai, Silky; Parker, Scott; McGirt, Matthew; Devin, Clinton; Cheng, Joseph
Introduction: Anterior cervical decompression and fusion (ACDF) is a most commonly used intervention in patients with myelopathy and radiculopathy. With growing elderly population and increasing rates of spinal surgery in this age group it is vital to understand the value of ACDF in this population. The aim of present study was to determine the cost-utility following ACDF for myelopathy and radiculopathy in elderly patients. Methods: A total of 299 patients undergoing elective ACDF with or without fusion for degenerative cervical pathology over a period of two-years, that were enrolled into prospective longitudinal registry were included in the study. PRO instruments: NDI, numeric rating scale-neck and arm pain (NP, AP), general health and quality of life scores via EQ-5D and SF-12 were recorded at baseline, 12-month and 24-month after surgery. One and two-year medical resource utilization, missed work, and health state values (quality-adjusted life years [QALYs], calculated from the EQ-5D with US valuation using time weighted area under the curve approach) were assessed. Two-year resource use was multiplied by unit costs based on Medicare national allowable payment amounts (direct cost). Patient and caregiver workday losses were multiplied by the self-reported gross-of-tax wage rate (indirect cost). The direct cost and total cost (direct + indirect) was used to assess mean total 2-year cost per QALY gained after surgery. The patients were divided into age groups (younger) < 65 years, and ≥ 65 years (older) to compare the QALYs gained and the cost-utility in this age groups. Results: There was a significant improvement in pain (NP, AP), disability (NDI) and general health scores (EQ-5D and SF-12) among all age groups 2-year after surgery ( p < 0.0001). Fifty-two percent (155) of patients underwent ACDF for myelopathy and 48% (144) underwent ACDF for radiculopathy; there was no significant difference in the number of patients with radiculopathy (42% vs 49%) and myelopathy (58% vs 51%) in patients ≥ 65 years compared with those < 65 years. The mean direct cost, and total cost at 24-month was 18, 828 and 23, 579 for younger patients and 19, 241 and 21, 197 for older patients. Younger patients had higher total cost at 24month due to higher workday losses; the direct cost was however higher in the older age group which was found to be associated with a higher mean number of co-morbidities (1.5 vs 2.7, p = 0.02) and mean longer hospital stay (1.2 vs 2.3 days, p = 0.018). Patients over 65 years old had a 33% preoperative gainful employment compared with 62% patients with age < 65 years. There was no statistically significant difference in mean direct cost among the younger and older patients. The younger patients had higher mean cumulative 2-year gain of 0.47 QALYs compared with 0.28 QALYs in older patients. The two-year direct cost-utility and total cost-utility in patients age < 65 years was 40, 059 and 50, 168/QALY compared with 68, 717/QALY and 75, 703/QALY in those ≥ 65 years. Conclusion: ACDF provided a significant gain in health state utility in elderly patients with degenerative cervical pathology, with a mean cumulative 2-year cost per QALY gained of 75703/QALY, which can be considered moderately cost-effective as per the threshold of 100, 000/QALY gained. Elderly patients do not see the degree of improvement as their younger counterparts; however, surgery does provide a clinically meaningful improvement.